Cinematography. Printed 8 mm Type S image area on 35 mm motion-picture film perforated 8 mm Type S, 2R-4.227 (1664) or 5R-4.234 (1667). Position and dimensions. (15th March 1996) - British Standards Institution,
No abstract available